2020
DOI: 10.1021/acs.jpcb.0c01680
|View full text |Cite
|
Sign up to set email alerts
|

Design of Nonideal Eutectic Mixtures Based on Correlations with Molecular Properties

Abstract: In this work, a statistical analysis was performed to reveal how the molecular properties are correlated with the nonideal behavior observed in eutectic mixtures. From this, a statistical model, combined with theory and experimental results, was developed to predict the nonideal behavior of a specific set of eutectic mixtures, consisting of quaternary ammonium bromides with dicarboxylic acids and polyols. The combination of this analysis and this model can be considered as a first step toward the a priori desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In the study by Xu et al, 42 key factors of DES pre-treatment of lignocellulosic biomass procedure were handled by principal component analysis (PCA) and partial least squares analysis methods to raise the possible efficiency of this industrial procedure [ 199 ]. Another case where PCA and regression analysis were used synergistically is the work of Kollau et al [ 200 ]. In this study, the authors used a combination of experimental, theoretical, and computed properties as input for their linear and non-linear models to predict the non-ideality of the DES mixtures and, thus, the eutectic temperatures.…”
Section: Simulation Methods For Dessmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Xu et al, 42 key factors of DES pre-treatment of lignocellulosic biomass procedure were handled by principal component analysis (PCA) and partial least squares analysis methods to raise the possible efficiency of this industrial procedure [ 199 ]. Another case where PCA and regression analysis were used synergistically is the work of Kollau et al [ 200 ]. In this study, the authors used a combination of experimental, theoretical, and computed properties as input for their linear and non-linear models to predict the non-ideality of the DES mixtures and, thus, the eutectic temperatures.…”
Section: Simulation Methods For Dessmentioning
confidence: 99%
“… Artificial neural network and genetic algorithm approach The feed-forward backpropagation neural network algorithm with 4 input layer neurons and 2 output layer neurons for 4 independent and 2 dependent variables. The optimum number of hidden layer neurons was 11 Experiment design for microwave-assisted extraction of phytochemical compounds from black jamun pulp [ 196 ] 12 DESs based on allyltriphenylphosphonium bromide: Triethylene glycol with molar ratios of 1:4, 1:10 and 1:16 Linear and quadratic regression models Estimation of carbon dioxide solubility in DESs [ 198 ] 13 DESs based on ChCl: Glycerol ChCl: P-coumaric acid Principal component analysis Partial least squares Furthermore, based on molecular simulation, the detailed relationships between key variables were further analyzed Revealing the biomass pretreatment mechanism by evaluating the inner relationships among 42 key process factors [ 199 ] 14 DESs based on tetraalkylammonium bromide Principal component analysis Regression analysis Prediction of DES eutectic temperatures [ 200 ] …”
Section: Table A1mentioning
confidence: 99%
“…It is also previously reported that the incorporation second component as HBD to the DES decreases T f where hydrogen bonding should become paramount with both components of DES (HBA and HBD) rather than a single component. 33,34 Therefore, the molar ratio 1 : 4 : 2.5 combination is selected further for all experiments and CO 2 capture applications. The details regarding the prepared DESs are presented in Scheme 1.…”
Section: Preparation Of Dessmentioning
confidence: 99%
“…In the study by Xu et al, 42 key factors of DES pretreatment of lignocellulosic biomass procedure were handled by principal component analysis (PCA) and partial least squares analysis methods to raise the possible efficiency of this industrial procedure [181]. Another case where PCA and regression analysis were used synergistically is the work of Kollau et al [182]. In this study, the authors used a combination of experimental, theoretical, and computed properties as input for their linear and non-linear models to predict the nonideality of the DES mixtures and thus the eutectic temperatures.…”
Section: Optimization Of Experiments Using MLmentioning
confidence: 99%